Transport phenomena of two-dimensional band carriers with Dirac-like energetic spectrum - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Conductivity of monolayer and bilayer graphene is considered with due regard
for mutual drag of band electrons and holes. Search of contribution of the drag to
conductivity shows that it sufficiently influences on mobility at high concentrations of
carriers, which belong to different groups and have different drift velocities. In bilayer
system the mutual drag can even change the direction of partial current.
Magnetoresistivity and Hall effect were theoretically investigated for neutral and gated
graphene. It is shown that for spatially unlimited neutral graphene Hall effect is totally
absent. In gated, exactly monopolar graphene for the same case effect of
magnetoresistivity vanishes; here the Hall constant does not involve any relaxation
characteristic in contrast to results obtained for the popular method of τ-approximation. It
is shown that limited sizes of crystal with monopolar conductivity can be cause for
impressive dependence of the Hall constant and magnetoresistivity on the value of
external magnetic field.